Nexus analysis between CPO production, carbon emissions and GDP: A case study in Indonesia - Hary Saputra Sundoro; Jovanny M. Suherman (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
Indonesia is the world's largest CPO producer, which can positively impact its economic fundamentals. However, clearing new land for CPO farming will have an impact in the form of carbon emissions. The amount of carbon emissions can have an impact on the Indonesian economy as well. Thus, the study aims to predict the relationship between the amount of CPO production, carbon emissions, and GDP in Indonesia. The study uses the VAR method. The annual data starts from 1980 to 2020. PCPO and CO2 are positively related, especially in the long term. PCPO and GDP also have a positive relationship, especially in the long term. The relationship between CO2 emissions and GDP is also positive in the long term. In the short term, the three variables are related lucratively. The most significant relationship is between PCPO and CO2 emissions. Public interest statement Understanding the relationship between CPO production, carbon emissions, and GDP is necessary, considering that Indonesia is the largest CPO producer. As the largest CPO producer, it will impact the economy. It will also have an impact on the creation of carbon emissions. Therefore, it is necessary to understand how those variables are related